Pendampingan Aktivitas Be a Digital Exporter Program Studi Independen Bersertifikat Pada Mitra Sekolah Ekspor Nasional - Hardi Alunaza; Mentari Mentari (I-Com: Indonesian Community Journal, 2024)
Students face various challenges related to international trade skills. These include a lack of practical understanding, cultural differences and communication skills, knowledge of export regulations and policies, adaptation to new technologies, negotiation skills, and foreign language proficiency. The Studi Independen is one of the Merdeka Belajar programs by the Ministry of Education and Culture. This project encourages students to collaborate with industries, ensuring that the curriculum learned by student is relevant to workforce needs. The community service activity in the form of the "Be A Digital Exporter" mentoring process is one of the Studi Independen activities that helps students improve their non-academic skills, such as communication, leadership, foreign languages, and teamwork. This community service activity was conducted over two months, from May to June 2024, using three methods, mentoring, consultation and evaluation, and reporting. The results of this mentoring activity showed an increase in understanding, as measured by initial and final assesment, covering eight competencies offered to students in the Studi Independen.